The Role of Central Banks in Inflation and Exchange Rate Stability Amidst Global Economic Challenges: Monetary Policy Approach - Juarsa, Eka; Janwari, Yadi; Hasanuddin, Muhammad; Ridwan, Ahmad Hasan; Athoillah, Mohamad Anton (Strata International Journal of Social Issues, 2025)
The global economic landscape poses significant challenges for developing countries, including Indonesia, particularly in managing inflation and exchange rate stability. This study investigates the role of central banks, with a specific focus on Bank Indonesia (BI), in maintaining economic stability amidst global economic uncertainties. Inflation, characterized by sustained price level increases and exchange rate fluctuations driven by international market dynamics and monetary policies, is identified as the primary concern affecting economic stability, purchasing power, and trade balance. The study highlights the pivotal role of BI’s inflation-targeting framework and adaptive monetary policy approaches in addressing these challenges and enhancing economic resilience. Using a qualitative descriptive analysis, the research draws on scholarly literature, official reports, and relevant academic sources to explore the effectiveness of BI’s strategies. Findings indicate that BI’s multifaceted role in inflation control and exchange rate management supports sustainable economic growth while adapting to global economic complexities. Recommendations emphasize the need for enhanced policy transparency, strategic collaboration with government and international stakeholders, and the development of adaptive monetary innovations to address digital disruptions and structural economic shifts. This study contributes to academic literature and offers actionable insights for strengthening Indonesia’s economic stability.